Lugar de criação e partilha. Um atelier de cerâmica no Paço da Ermida - Francisca Sarrico Vieira Teixeira Carneiro (2023)
As the title itself states - "Place of creation and sharing. A ceramics atelier in the Paço da Ermida" - this dissertation seeks to respond to a project request, reflecting on the space that enables the creation and sharing of a particular art, ceramics, in the region of Ílhavo, more specifically in the Paço da Ermida. Thus, through the acquisition of the necessary knowledge about the circumstance of the place, ceramics and the definition of the program - a museum and an atelier - it seeks to reflect in project form about the hypotheses that best answer the need to relate the existing with the programmatic demands that buildings require.